The effect of service quality, brand image and price perception of IM3 prepaid card on customer satisfaction in central Jakarta - Muhammad Ivan Randika; Olivia Yolanda (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2021)
Along with the increasing need, communication service providers also face high demands, where consumers need fast internet access, and a vast network will be the first choice. Therefore, the factors affecting customer satisfaction become the primary concern of communication service providers. This study describes the importance of service quality, brand image, and price perception in influencing prepaid phone card user satisfaction among young people in Jakarta. Using a case study on 180 customers in Jakarta, the research findings provide evidence in line with the allegations. Service quality and brand image are two factors that positively affect consumer satisfaction, while the perceived price is not proven as an antecedent of satisfaction. This finding indicates that price perception is not a concern of consumers as long as service quality and the brand image they consider to be fulfilled when using communication services.